2021
DOI: 10.1038/s41467-021-22580-8
|View full text |Cite
|
Sign up to set email alerts
|

Orally delivered MK-4482 inhibits SARS-CoV-2 replication in the Syrian hamster model

Abstract: The COVID-19 pandemic progresses unabated in many regions of the world. An effective antiviral against SARS-CoV-2 that could be administered orally for use following high-risk exposure would be of substantial benefit in controlling the COVID-19 pandemic. Herein, we show that MK-4482, an orally administered nucleoside analog, inhibits SARS-CoV-2 replication in the Syrian hamster model. The inhibitory effect of MK-4482 on SARS-CoV-2 replication is observed in animals when the drug is administered either beginnin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 45 publications
(65 reference statements)
5
147
0
6
Order By: Relevance
“…Since Molnupiravir is a prodrug which is, after absorption, rapidly converted into its active metabolite EIDD-1931 [10], we quantified this metabolite in the plasma samples at the same time point as for Favipiravir. Very low concentration of EIDD-1931 were detected in the plasma samples (average of 37 and 78 nM in the single and combination treatment groups, respectively), which is most likely attributed to the fact that the activation of Molnupiravir occurs mainly in tissues [10].…”
Section: The Combined Molnupiravir/favipiravir Treatment Enhances the In Vivo Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Since Molnupiravir is a prodrug which is, after absorption, rapidly converted into its active metabolite EIDD-1931 [10], we quantified this metabolite in the plasma samples at the same time point as for Favipiravir. Very low concentration of EIDD-1931 were detected in the plasma samples (average of 37 and 78 nM in the single and combination treatment groups, respectively), which is most likely attributed to the fact that the activation of Molnupiravir occurs mainly in tissues [10].…”
Section: The Combined Molnupiravir/favipiravir Treatment Enhances the In Vivo Efficacymentioning
confidence: 99%
“…Incorporation into viral RNA results in the accumulation of deleterious transition mutations beyond a permissible error threshold to sustain the virus population, leading to error catastrophe [7,8]. The orally bioavailable, pro-drug counterpart of NHC [9], Molnupiravir (EIDD-2801, MK-4482) was shown to result in an antiviral effect against SARS-CoV-2 in a Syrian hamster model [10], in a mouse model [11] and in ferrets [12]. Data from a first-in-human, phase 1, randomized, double-blind, placebo-controlled study in healthy volunteers indicate that the drug is well tolerated and that plasma exposures exceed the expected efficacious doses based on scaling from animal models [13].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that molnupiravir is not a chain terminator may explain the mechanism by which it eludes the proofreading function of coronavirus exonucleases. Biochemical and deep sequencing studies have confirmed that viral mutagenesis is the main mechanism by which molnupiravir inhibits coronaviruses ( 28 , 46 , 47 ). NHC can be metabolized into deoxy-NHC and cause DNA mutations in host cells ( 48 ).…”
Section: Polymerase Inhibitorsmentioning
confidence: 98%
“…Molnupiravir has broad-spectrum antiviral activity against multiple viruses, including SARS-CoV, MERS-CoV, and SARS-CoV-2, with most EC 50 s below 1 μM ( 28 , 49 ). It is active in primary human airway epithelial cells, and it reduces virus levels, disease, and lung damage in mouse models of SARS-CoV and MERS-CoV ( 28 , 50 ) and in hamster ( 46 ) and ferret models ( 51 ) of SARS-CoV-2. Two first-in-human pharmacokinetic studies have been performed, including a phase 1 dose-ranging study of a 5-day course of oral therapy in healthy adults ( 52 ) and phase 1b/2a dose-escalating placebo-controlled trials among adult COVID-19 outpatients within 5 days of symptom onset ( 53 ).…”
Section: Polymerase Inhibitorsmentioning
confidence: 99%
“…In cell culture J o u r n a l P r e -p r o o f assays, molnupiravir was found to be a potent inhibitor of SARS-CoV-2 replication with an EC 50 in the submicromolar range (3,4). This inhibitory effect was also observed in animal models such as Syrian hamsters and humanized mice (5,6), and NHC administration to infected ferrets prevented SARS-CoV-2 transmission to untreated and uninfected animals (7). Molnupiravir is currently in phase II/III clinical trials based on encouraging preclinical data and its lack of toxicity and adverse side effects in phase I clinical trials.…”
mentioning
confidence: 93%